Investment risk allocation and the venture capital exit market: Evidence from early stage investing - Chaplinsky, Susan; Gupta-Mukherjee, Swasti (Journal of Banking & Finance, 2016)
This study provides evidence on how venture capitalists’ (VCs’) allocations of capital to riskier investments, as measured by the proportion of early versus late-stage investment in an industry, are linked to exit market conditions. Prior research has primarily focused on how VCs adjust aggregate investment to public equity market conditions. We develop a more inclusive measure of exit market conditions that accounts for recent secular changes that have affected the industry return structure, specifically, the sharp rise in the number of failures and M&A relative to IPO exits. We show that the dollars gained relative to dollars lost in recent exits and failures are significantly positively related to VCs’ allocations to early-stage companies over the period 1990–2008. The changes in allocations are large enough to have an effect on the availability of funding for early stage companies. In sum, our evidence shows that exit market conditions have a significant and economically meaningful influence on VCs’ allocations to riskier investments.